BODY COMPOSITION OF PATIENTS WITH SUBCLINICAL THYROID DYSFUNCTIONS (Fiep Bulletin - online, 2010)
Subclinical hyperthyroidism (SCH) and subclinical hypothyroidism (SH), also called subclinical thyroid dysfunctions, are characterized by serum concentrations of thyroid hormones within the normal range, associated, respectively, with suppressed or increased serum TSH levels. It is not well-established if SCH or SH patients also present changes in body composition, similar to those observed in the clinical forms of the diseases. The aim of the study was to evaluate the body composition of SCH and SH patients. A cross-sectional study was performed with 34 women with subclinical hyperthyroidism (SCH) on TSH-suppressive therapy with levothyroxine (LT4) for differentiated thyroid carcinoma, 23 with subclinical hypothyroidism (SH) and 43 without thyroid disease (EU). The body composition was assessed by the anthropometric method and the following parameters were analyzed: Body Mass Index (BMI; kg/m2); Body fat percentage (% BF), the sum of seven skinfolds thickness, Lean Mass and Muscle mass. Descriptive analyzes were shown as median and 25th and 75th percentiles (interquartile range). The comparisons between SCH patients, SH patients and controls were made by using the Kruskal-Wallis Test and the differences were obtained by the Mann-Whitney U-test with Bonferroni correction (SPSS 13.0). Significance level: p0.05. Results: No differences were found among the groups in relation to total body fat, as well as its distribution. SCH patients presented lower thigh girth (SCH = 51.7 (47.9 – 56.0) cm vs. EU = 53.7 (51.0 – 57.0) cm; p=0.05) and muscle mass (SCH = 20.8 (18.5 – 23.9) kg vs. EU = 22.5 (19.8 – 24.5) kg; p =0.05) when compared to controls. Conclusion: Our results suggest that only SCH is associated with changes in body composition, similar to those observed in clinical hyperthyroidism.
Keywords: body composition; subclinical hyperthyroidism; subclinical hypothyroidism